2010
DOI: 10.1007/s12072-010-9223-1
|View full text |Cite
|
Sign up to set email alerts
|

Liver stiffness measurement in the risk assessment of hepatocellular carcinoma for patients with chronic hepatitis

Abstract: Backgroud/aims The risk of hepatocellular carcinoma (HCC) increased with progression of hepatic fibrosis as assessed by liver stiffness measurement (LSM). This study used LSM to assess the risk of HCC presence in patients with chronic hepatitis. Methods The patients with liver tumor or chronic hepatitis indicated for biopsy were prospectively enrolled. LSM was performed on the same day as biopsy. The diagnostic performances of clinical parameters and LSM in predicting HCC presence were compared with the areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 30 publications
2
28
1
Order By: Relevance
“…The relationship between presence or absence of HCC and liver stiffness was investigated by Masuzaki et al 9 . in a group of hepatitis C patients, by Kuo et al 13 . in a group of hepatitis B and hepatitis C patients, and by Nahon et al 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between presence or absence of HCC and liver stiffness was investigated by Masuzaki et al 9 . in a group of hepatitis C patients, by Kuo et al 13 . in a group of hepatitis B and hepatitis C patients, and by Nahon et al 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of liver stiffness by transient elastography is a rapid, noninvasive, and reproducible method that reportedly offers an accurate representation of the extent of hepatic fibrosis in viral hepatitis and non‐alcoholic steatohepatitis 1–8 . However, few reports have examined the relationship between liver stiffness measurements by transient elastography and hepatocellular carcinoma (HCC) 9–13 . This study investigated the value of liver stiffness in diagnosing HCC among patients with viral hepatitis, and prospectively investigated the relationship between liver stiffness and HCC development.…”
Section: Introductionmentioning
confidence: 99%
“…It appears that in this subgroup of patients, the absolute LS value at baseline or 10‐year follow‐up, rather than the magnitude of fibrosis regression, was more important with respect to risk of cirrhosis and HCC. LSM has been incorporated into HCC risk prediction models . However, whether these models can be applied in NA‐treated patients is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…revealed that liver stiffness measurement using transient elastography was strongly associated with the probability of the presence of HCC among patients with hepatitis C in a cross‐section setting 30 . The usefulness of transient elastography for the estimation of predicting the risk of HCC development was also suggested in other cross‐sectional setting studies, intended for patients with hepatitis B and C, and for patients with hepatitis C and alcoholic liver disease 10,31 . On the other hand, prospective cohort studies published previously, with respect to the association between liver stiffness measured by transient elastography and the risk of HCC development, consist of only two papers at present.…”
Section: Prediction Of Hcc Development By Transient Elastographymentioning
confidence: 90%